2021
DOI: 10.1007/s12639-021-01367-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminth parasites in domestic ruminants from Srikakulam district, Andhra Pradesh, India

Abstract: Coprological studies on the prevalence of gastrointestinal helminth (GI) parasites in domestic ruminants from Srikakulam district of Andhra Pradesh, India, were carried out for a period of one year from January 2019 to December 2019. Fecal examination was done using direct smear, sedimentation and oatation methods. Altogether 3,527 fecal samples were examined including 595 from cows, 485 from buffaloes, 1342 from sheep and 1105 from goat. Out of 3,527 fecal samples examined, 1084 were found to be positive with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(14 reference statements)
1
4
0
1
Order By: Relevance
“…Seasonal prevalence of helminth parasites revealed that the highest infection rate in cattle and sheep was in the winter season, of highly significant difference (p< 0.01). These findings in cattle agree with the previous study by Malathi et al, (2021) who reported that the highest infection rate was in the winter season (53.64%), but the current study in contrast to the previous reports by Kumar et al, (2016) and Shit et al, (2017) in India who found that the highest infection rate was in summer and rainy season, respectively. In sheep, the current study disagrees with two studies in India by Tramboo et al, (2015) who stated that the highest infection rate was in summer season and Dappawar et al, (2018) who found that the highest infection rate was in autumn season.…”
Section: Discussionsupporting
confidence: 91%
“…Seasonal prevalence of helminth parasites revealed that the highest infection rate in cattle and sheep was in the winter season, of highly significant difference (p< 0.01). These findings in cattle agree with the previous study by Malathi et al, (2021) who reported that the highest infection rate was in the winter season (53.64%), but the current study in contrast to the previous reports by Kumar et al, (2016) and Shit et al, (2017) in India who found that the highest infection rate was in summer and rainy season, respectively. In sheep, the current study disagrees with two studies in India by Tramboo et al, (2015) who stated that the highest infection rate was in summer season and Dappawar et al, (2018) who found that the highest infection rate was in autumn season.…”
Section: Discussionsupporting
confidence: 91%
“…The distribution of rumen fluke infecting ruminants has been well documented globally owing to the economic importance from the veterinary standpoint (Huson et al, 2017;Nisar et al, 2021;Pfukenyi & Mukaratirwa, 2018), with a broad geographical spread, particularly in Nigeria, Thailand, and India (Dube, 2010;Kaewnoi et al, 2020;Malathi et al, 2021). Different rumen fluke species predominated in other parts of the world (Rafiq et al, 2020).…”
Section: Epidemiological Factors Of Rumen Fluke In Cattle and Buffaloesmentioning
confidence: 99%
“…The common species of snails that can act as intermediate hosts of rumen fluke reported from different Asian countries include Radix rubiginosa, Radix auricularia, Lymnaea truncatula, Lymnaea stagnalis, Lymnaea natalensis, Lymnaea palustris, Lymnaea viridis, Lymnaea luteola, Bulinus truncates, Bulinus furskalii, and Indoplanorbis exustus (Dodangeh et al, 2019;Dung et al, 2013;Martin & Cabrera, 2018;Mohammed et al, 2016). Therefore, rumen fluke is found at high prevalence in most tropical and sub-tropical countries such as Bangladesh, Thailand, Indonesia, and India (Azam et al, 2012;Kaewnoi et al, 2020;Hambal et al, 2020;Malathi et al, 2021), particularly in locations where the climatic and environmental conditions are favourable for the intermediate host snail's survival and multiplications (Gordon et al, 2013;Taylor et al, 2007). Also, these intermediate hosts play an essential role in completing the life cycle of rumen fluke and transmitting the disease (Lotfy et al, 2010;Pfukenyi & Mukaratirwa, 2018).…”
Section: Snail Intermediate Hostmentioning
confidence: 99%
“…Infection of GI parasites found in this study was also higher when compared to buffalo in other Asian countries. Malathi et al [17] reported that Nematode infection in buffalo in India was 5.06%. Slightly different results were reported by Williams [18], that the prevalence of Nematode, Cestode, and Protozoal oocysts in Punjab, Pakistan were 29.55%, 1.36%, and 5.35%, respectively.…”
Section: Thementioning
confidence: 99%